Gerhard Mercator: Kommentar zum Römerbrief (Kapitel 1-11) - Mercator, Gerhard (Studies in medieval and Reformation traditions, 2026)
"Gerhard Mercator's (1512-1594) main theological work, previously available only in manuscript form, is presented here for the first time in a critical edition with a German translation. The commentary on the Epistle to the Romans (chapters 1-11) reveals the Duisburg cartographer to be an independent theologian. Engaging critically with the predestination doctrine of John Calvin and Theodor Beza, Mercator defends man's freedom of will and the unconditional goodness of God. His 'doctrinal' interpretation of St. Paul's text sheds light on new previously unexplored aspects of his theological and philosophical thought. This bilingual edition is a valuable source not only for reconstructing the religious foundation of this early modern scholar, but also for researching the cultural conditions under which modern science emerged"-- Provided by publisher